2008
DOI: 10.1136/bjo.2008.137471
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fibre layer thickness measurements using optical coherence tomography in migraine patients

Abstract: The RNFL in the temporal quadrant was found to be thinner in migraine patients. In addition, we found a strong correlation between migraine severity and the RNFL average thickness parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
106
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 34 publications
6
106
1
Order By: Relevance
“…9,10 It is noteworthy that RNFL is used as a simple test to evaluate headache progression over time.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 It is noteworthy that RNFL is used as a simple test to evaluate headache progression over time.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that RNFL thinning occurs at different quadrants, and there are also studies regarding the relation between migraine and retrobulbar blood flow alterations. [15][16][17][18][19][20][21] According to Kara et al, 30 the retrobulbar circulation and flow haemodynamics in the left vertebral artery may be altered in both headache and headache-free periods in migraineurs without aura. Glenn et al 31 reported a case of complicated migraine due to bilateral retinal infarction.…”
Section: Discussionmentioning
confidence: 99%
“…2,[7][8][9][10][11][12][13][14] Also, there are studies supporting the ischaemic theory by focusing on the retinal nerve fibre layer (RNFL) thickness detected by optical coherence tomography (OCT) on migraine patients and studies demonstrating that the retina and cerebral structure of migraine patients are affected. [15][16][17][18][19][20][21] In the present study, we used OCT to determine whether RNFL thickness is related to the presence of cerebral WML in migraine patients. Thus, we aimed to evaluate an anatomical relationship of RNFL thickness to MRI findings in migraine patients.…”
Section: Introductionmentioning
confidence: 99%
“…Today, modern technological OCT devices are employed for the in vivo quantitative measurement of the peripapillary RNFL, GCL, and choroid layer in various neuro-ophthalmological diseases. The reduction in RNFL thickness reflects the loss of ganglion cells and axons in migraine patients (4)(5)(6) . We expected the retina and optic nerve to be affected in recurrent migraine attacks with aura due to hypoperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral blood flow in the occipital hemisphere has been shown to diminish during migraine attacks, especially in migraine with aura. Hypoperfusion has been reported to affect the retina and the optic nerve, as well as result in ganglion cell loss (4) . The retinal nerve fiber layer (RNFL) contains the axons of the retinal ganglion cells.…”
Section: Introductionmentioning
confidence: 99%